Nitrogen dioxide and ammonia gas molecules interaction studies on phosphorene nanosheet — a DFT investigation - Nagarajan, V.; Chandiramouli, R. (Condensed Matter Physics, 2019)
The adsorption behaviour of hazardous gas molecules, namely nitrogen dioxide (NO₂ ) and ammonia (NH₃), on phosphorene nanosheet (PNS) was explored by means of ab initio technique. To improve the structural solidity of pristine PNS, we have introduced the passivation of hydrogen and fluorine at the terminated edge. The structural solidity of both hydrogen and fluorine passivated PNS is verified in terms of formation energy. The main objective of this research work is to probe NO₂ and NH₃ gases using PNS as a base sensing material. The adsorption of various preferential adsorption sites of these gas molecules is studied in accordance with the average HOMO-LUMO gap changes, natural-bond-orbital (NBO) charge transfer, HOMO-LUMO gap, and adsorption energy. Notably, the negative value of adsorption energy is found upon the adsorption of NO₂ and NH₃ on PNS and it is in the range of −1.36 to −2.45 eV. The findings of the present research work recommend that the hydrogenated and fluorinated PNS can be effectively used as a chemical sensor against NO₂ and NH₃ molecules.